2020
DOI: 10.3390/ijms21238909
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Dopamine Receptor Signaling

Abstract: The renal dopaminergic system has been identified as a modulator of sodium balance and blood pressure. According to the Centers for Disease Control and Prevention, in 2018 in the United States, almost half a million deaths included hypertension as a primary or contributing cause. Renal dopamine receptors, members of the G protein-coupled receptor family, are divided in two groups: D1-like receptors that act to keep the blood pressure in the normal range, and D2-like receptors with a variable effect on blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 106 publications
(132 reference statements)
0
13
0
Order By: Relevance
“…Of note, this list should also be complemented with biochemical factors not specific to the receptor itself, but of its environment. Indeed, it is relevant to note that dopamine receptors are not homogenously distributed across the cell membrane but are mainly located in membrane microdomains determined by lipid rafts 41 . Hence, it is possible that increased D 2L receptor density might have an impact on receptor organization and distribution across such defined membrane compartments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, this list should also be complemented with biochemical factors not specific to the receptor itself, but of its environment. Indeed, it is relevant to note that dopamine receptors are not homogenously distributed across the cell membrane but are mainly located in membrane microdomains determined by lipid rafts 41 . Hence, it is possible that increased D 2L receptor density might have an impact on receptor organization and distribution across such defined membrane compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is relevant to note that dopamine receptors are not homogenously distributed across the cell membrane but are mainly located in membrane microdomains determined by lipid rafts. 41 Hence, it is possible that increased D 2L receptor density might have an impact on receptor organization and distribution across such defined membrane compartments. Given the importance of lipid rafts in the determination of dopamine receptor signaling, 41,42 further research should integrate their existence in mechanistic models.…”
Section: D2l Receptor Overexpression Reorients the Recruitment Bias O...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple possible explanations for this observation. The first one is that, the overlapping activity of other kinases, conceivably Src-family kinases like Lyn, may substitute for Syk when it is inhibited, by phosphorylating the suggested target in this pathway, Cbl (Cbl/Cbl-b) ( 50 ). A second possibility is that, as the antibody used for the assessment of CD11b activation (commercial mAb CBRM1/5) did not recognize its intermediate affinity state, such a change was not quantified even though it may also be a consequence of triggering the CD13-CR3 signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies based on the conformational order of lipids and differences in their short-range translation proved the existence of heterogeneity and structurally and functionally organized regions in the biological membrane, which are termed lipid rafts [4]. They are enriched in sphingolipids with a predominance of simple hydrocarbon chains, cholesterol, glycosphingolipids, and proteins forming specific platforms or lipid microdomains [5]. It was found that different ratios of lipids in the rafts affect the fluidity of the membrane [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%